THE “OTHER” IMAGE: A TIME-PLACE RIFT IN THE LEBANESE IDENTITY (Proceeding of the International Conference on Arts and Humanities, 2019)
In May 2018, the British photographer Chris Coekin and the Lebanese photographer Noel Nasr published a collaborative body of work entitled “The Distance is Always Other.” Inspired by an archive produced in 1973 by an elderly couple of American tourists known as Bob and Ann, the archive is a curious mix of vernacular images documenting the Lebanese landscape. The images were produced with a basic stereoscopic camera where two photographs were produced simultaneously through two separate lenses, resulting in two images depicting the same viewpoint. Coekin and Nasr retraced the footsteps of the tourists, applying the idea of two separate images. They each used identical vintage fixed-lens film cameras but with Coekin operating as the left lens while Nasr was the right. Their two final images were overlaid together to form one single image. The visually appealing aesthetic represents the artists’ ambitious but flawed attempt to faithfully record the same image, raising questions about the representational limitations of the photograph, whilst engaging the viewer in a unique and intriguing story. In a critical reading of this work, this paper argues that the images produced were conceptualized around the notion of “other”: the other individual, the other time and the other place. It furthermore proposes that this otherness bears a strong resemblence to the Lebanese (cultural) identity crisis and complexity. Moreover, the paper argues that the “The Distance is Always Other” signifies a contextual drift; a drift in space and time, hence a quasi-gaze which consolidates the quasi-identity of the Lebanese.
Keywords: vernacular photography; Lebanon; other; identity rift